A research review: how technology helps to improve the learning process of learners with dyslexia - Chai, Jing Ting (Universiti Malaysia Sarawak (UNIMAS), 2015)
Dyslexia is a language disorder that leads to difficulty with words and it is the most common type of learning disability. This study is a systematic review on the current state of technologies used in improving the learning process of learners with dyslexia. A total of twenty-five journals articles and international conference papers published between 2000 and 2014 were included in the review. The research articles were collected from twelve databases and being analyzed according to cyclical process. The findings show that majority of the studies focused on children and adolescents. There are four main research themes derived and discussed for the technologies used in the learning process of learners with dyslexia, namely, text-to-speech technologies, eye-tracking technologies, virtual learning environments, and games. Additionally, there are another four main research themes revolve around the purpose of the assistive technologies, namely, reading, writing, memory, and mathematics. Furthermore, text-to-speech technology is the most common technology used by learners with dyslexia. Moreover, a majority of the studies mention and focus the use of technologies on the improvement of reading in learners with dyslexia. This study is expected to provide a clearer view on the current state of technologies used in improving the learning process of learners with dyslexia.